2012
DOI: 10.21236/ada619014
|View full text |Cite
|
Sign up to set email alerts
|

Deployment Surveillance Summary, U.S. Army Operation Iraqi Freedom/Operation New Dawn/Operation Enduring Freedom, 2010

Abstract: Report Documentation PageForm Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Publications contributing to the theme of suicide-related events management ( n = 8) 21 , 22 , 25 , 32 , 55 , 62 , 69 , 70 confirmed that the most severe mental health AEs are for suicidal ideation and suicidal gestures, 7 , 22 that self-harm is the strongest predictor for AE, 25 and that self-harm is a serious contributor to in-theater mortality. 21 , 32 , 70 Furthermore, epidemiologic surveillance methodology may not accurately capture the true burden of mental illness on AE and the military health system due to some suicides and suicide attempts coded as injury/poisonings per ICD-9/10 coding conventions.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Publications contributing to the theme of suicide-related events management ( n = 8) 21 , 22 , 25 , 32 , 55 , 62 , 69 , 70 confirmed that the most severe mental health AEs are for suicidal ideation and suicidal gestures, 7 , 22 that self-harm is the strongest predictor for AE, 25 and that self-harm is a serious contributor to in-theater mortality. 21 , 32 , 70 Furthermore, epidemiologic surveillance methodology may not accurately capture the true burden of mental illness on AE and the military health system due to some suicides and suicide attempts coded as injury/poisonings per ICD-9/10 coding conventions.…”
Section: Resultsmentioning
confidence: 89%
“…Seven of the nine epidemiologic surveillance articles were MSMRs describing psychiatric AE rates during operations Iraqi Freedom, Enduring Freedom, and New Dawn. 1–4 , 21 , 32 , 57–60 The rates of AE from theater fluctuated over the decades, rising with associated mission activity. Psychological AEs increased by 50% from a rate of 6-9% in 2001-2005 to 16% by 2009 57 with a peak of 28% during 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the American triumph was largely attributed to the completely novel approach of conducting military operations aided by psychological operations (PSYOPS) at that time. Such coordinated action (kineticpsychological) effectively led to the surrender of many units without engaging the advancing enemy 467 . As a result, only a part of the Iraqi troops took up the fight, putting up relative resistance (including the tank battle of Basra, the battles for Al-Hilli and Karbala) and relatively strong resistance during the fights for Baghdad 468 threats and threats resulting from activities below the threshold of war with the use of military means.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the American triumph was largely attributed to the completely novel approach of conducting military operations aided by psychological operations (PSYOPS) at that time. Such coordinated action (kineticpsychological) effectively led to the surrender of many units without engaging the advancing enemy 467 . As a result, only a part of the Iraqi troops took up the fight, putting up relative resistance (including the tank battle of Basra, the battles for Al-Hilli and Karbala) and relatively strong resistance during the fights for Baghdad 468 threats and threats resulting from activities below the threshold of war with the use of military means.…”
Section: Discussionmentioning
confidence: 99%